The hidden history of Head Start - Zigler, Edward, 1930-; Styfco, Sally J. (New York ; Oxford : Oxford University Press, 2010)
Currently enrolling 900,000 poor children each year, Head Start has served 25 million children and their families since it started 43 years ago. Despite its longevity and renown, much of Head Start's story has never been told, and this book gives a detailed account of the remarkable program.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Head Start Program (U.S.) -- History; Early childhood education -- United States -- History